KUALITAS LINGKUNGAN PERMUKIMAN KAWASAN INDUSTRI DI KECAMATAN GENUK KOTA SEMARANG - Septi Ayuningtyas; Bitta Pigawati (Diponegoro University, 2019)
The increase in the number and activity of the population implies increasing the area woke up, especially for the neighborhood. There are a variety of different settlement environment character in the suburban area of Semarang. The existence of settlements in district Genuk which is in the industry and affected rob feared decline of environmental quality neighborhoods. There are still many residents living in the northern part of Kecamatan Genuk flooded rob and decline the face of the land. The condition can have implications for environmental degradation in neighborhoods in district Genuk.Research on environmental quality neighborhoods in district Genuk aims to analyze the changes in environmental quality neighborhoods, using a spatial approach to the method of remote sensing and Geographic Information System (GIS). Analytical techniques weighted overlay using the variable density of settlements, the layout of the buildings, the condition of the wide driveway, driveway, tree protectors, the location of settlements and the quality of the roof of the building refers to the assessment of the Department of public works. Results show that for 10 years of environmental degradation has occurred in district neighborhoods Genuk, namely in Sembungharjo Village and Genuksari Village. This occurs due to the increased density of settlements and the decline of the tree protectors.